Heavy metal contamination in vegetables and its detection: a review - Mohd Ruzaidy, Nur Illia; Amid, Azura (Zibeline International, 2020)
The quality of marketed vegetables cannot be guaranteed as many of them has been contaminated with heavy metals such as lead, cadmium and arsenic. These heavy metals can act as either growth supporter or threat depending on their types and amount absorbed by the plants. The consumption of an excessive amount of heavy metals in vegetable may cause several diseases such as renal dysfunction and bone depletion. There are few methods used to detect heavy metal contamination such as Atomic Absorption Analysis (AAS), Neutron Activation Analysis (NAA), X-ray Fluorescence Spectroscopy (XRF) and Inductively Coupled Plasma Spectrometry (ICPMS). This paper discusses all these methods to compare their efficiency, advantages and disadvantages to select the best method for heavy metal detection in vegetables.